SEAWEED EXTRACTS IMPROVE LIPID PROFILE OF WISTAR RAT - Marhaeni Julyasih, K. Sri; Suata, K.; Wirawan, I.G.P; Mantik Astawa, I. N. (INDONESIAN JOURNAL OF BIOMEDICAL SCIENCES; Vol. 5, No. 2 Mei 2011, 2012)
Hypercholesterolemia or hyperlipidemia has been established as an important risk factor of cardiovascular disease. Patients with hypercholesterolemia usually require a prolonged treatment; and the newer and more potent generation of antilipid agents are costly.In Bali there are several types of seaweed that are generally consumed by the local people and known by the local names of Bulung Boni (Caulerpa spp.) and Bulung Sangu (Gracilaria spp.). Preliminary studies on the effect of Bulung Boni and Bulung Sangu extracts appeared to improve lipid profile, but the available data are still very limited both in extent and depth, and further investigations were considered relevant and needed.This experimental study used completely blind randomized design, using a total of 24 Wistar rats divided into six sample groups of equal size, all fed with a diet high in cholesterol content. The six sample groups were respectively designated as negative control group, positive control group, and four treated sample groups, respectively fed orally with a dose of 20 mg and 60 mg extracts of Bulung Boni per 100g of body weight per day, and 20 mg and 60 mg extracts of Bulung Sangu per 100g body weight per day. Each treatment was repeated four times.Our study showed that rats fed with high-cholesterol diet and treated with oral Bulung Boni or Bulung Sangu extract at a dose of 20 mg and 60 mg/100 g bw/ day were associated with statistically significantly increased plasma HDL levels (p < 0.05), and statistically significant decreased plasma LDL and total cholesterol levels (p < 0.05) as compared with those of rats fed with high cholesterol diet without treatment with Bulung Boni or Bulung Sangu extracts.From our data it could be implied that Bulung Boni and Bulung Sangu extracts improve lipid profile in the Wiatar rat by significantly increasing plasma HDL level, and lowering LDL and total cholesterol levels.
Keywords: Seaweed extracts, Caulerpa spp, Gracilaria spp, HDL cholesterol, LDL cholesterol, total cholesterol, and anti-lipid agent